Profitability, farmer and farm characteristics: the case of Ghana broiler chicken industry in 2015 - Ekong, Olabisi Aderonke (Kansas State University, 2018)
This study assessed the farm and farmer characteristics influencing the profitability of broiler chicken farms in Ghana. It used data obtained from the 2015 census of the poultry industry conducted by USAID-METSS in collaboration with Ghana's Ministry of Food and Agriculture and the Ghana National Association of Poultry Farmers. Results show that broiler production in Ghana is operated on a small scale basis with an average number of 1,410 birds. Broiler chicken production is profitable in Ghana with national average gross margin/bird of GHS 9.22 and standard deviation of 8.40. Regression analysis was carried out using Ordinary Least Square method to estimate the effect of farm and farmer characteristics on profitability and also explore regional differences. Results shows that farm income and feed were negative and statistically significant such that a farmer with primary income from broiler chicken production had a decrease in gross margin of GHS 1.24 per bird compared to a farmer with other sources of income; a farmer that increases one unit of own feed production will have a decrease in gross margin of GHS 0.06 per bird. Additionally, regional differences exist such that farms situated in Ashanti, Central, and Eastern had higher gross margin per bird of GHS 3.21, GHS 6.10 and GHS 6.26 respectively compared to farms situated in Brong Ahafo Region. In conclusion, the study shows that both farmer (primary source of income) and farm characteristics (such as regional location and the extent to which feed was prepared on the farm) were important in explaining broiler chicken profitability. Finally, continuous research is recommended to examine the robustness of these factors in explaining profitability.
Keywords: Gross margin; Profitability; Broiler chicken production; Farm characteristics; Farmer characteristics; Ghana